2018
DOI: 10.9767/bcrec.13.3.1956.489-501
|View full text |Cite
|
Sign up to set email alerts
|

Green Biofuel Production via Catalytic Pyrolysis of Waste Cooking Oil using Malaysian Dolomite Catalyst

Abstract: Malaysian Dolomite has shown potential deoxygenation catalyst due to high capacity in removing oxygen compound and produce high quality of biofuel with desirable lighter hydrocarbon (C8-C24). The performance of this catalyst was compared with several commercial catalysts in catalytic pyrolysis of Waste Cooking Oil. Calcination at 900 °C in N2 produced catalyst with very high activity due to decomposition of CaMg(CO3)2 phase and formation of MgO-CaO phase. The liquid product showed similar chemical composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Moreover, based on Diwald et al [103], the strength of the basic sites of the alkaline earth metal oxides studied in temperature-programmed desorption (TPD) of CO2 increased in the order of MgO < CaO < SrO < BaO. In addition, the MgO ions were reported among several basic oxides (such as La2O3, CeO2, or ZrO2), which were successful in min- Meanwhile, Raja et al [101], reported that MgO played an important role in increasing oil quality by reducing oxygen levels and converting almost all the long chain alkanes and alkenes to low molecular weight hydrocarbons in the diesel range. The potential of MgO as a based catalyst was proved by Tani et al [102], due to its significant role in increasing the oil quality by reducing oxygen levels and directly reducing the acid values and iodine values of the cracking oil, which was suitable to be used in diesel engine vehicles.…”
Section: Thermal-activated (Calcined) Dolomite Catalystsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, based on Diwald et al [103], the strength of the basic sites of the alkaline earth metal oxides studied in temperature-programmed desorption (TPD) of CO2 increased in the order of MgO < CaO < SrO < BaO. In addition, the MgO ions were reported among several basic oxides (such as La2O3, CeO2, or ZrO2), which were successful in min- Meanwhile, Raja et al [101], reported that MgO played an important role in increasing oil quality by reducing oxygen levels and converting almost all the long chain alkanes and alkenes to low molecular weight hydrocarbons in the diesel range. The potential of MgO as a based catalyst was proved by Tani et al [102], due to its significant role in increasing the oil quality by reducing oxygen levels and directly reducing the acid values and iodine values of the cracking oil, which was suitable to be used in diesel engine vehicles.…”
Section: Thermal-activated (Calcined) Dolomite Catalystsmentioning
confidence: 99%
“…As studied by Hafriz et al [ 95 ], dolomite catalysts have indicated maximum biofuel conversion for catalytic reactions at optimum condition of 410 °C, 60 min, 5.50 wt% of catalyst loading, and 175 cm 3 /min of N 2 . The higher temperature could slow the cracking activity and induce major vaporization from the conversion reaction, which would reduce the biofuel producibility [ 86 , 101 ].…”
Section: Dolomite Catalyst Key Elements For Upgrading Biofuel Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Buyang, et al [10] used dolomite directly as a catalyst in the pyrolysis of Reutealis trisperma oil to produce a liquid yield of 77.39%. The basic site composition of CaO and MgO contained in dolomite is able to support the deoxygenation reaction through pyrolysis and increase hydrocarbons, increasing their cracking into lighter and heavier organic fractions [11]. The ketonization reaction of carboxylic acid converts it into a ketone and some oromatic and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%